Draft Annual Plan 1982-83 Administration of Union Territory of Dadra and Nagar-Haveli - Planning Commission (Planning Commission, 1982)
Dadra and Nagar Haveli is a small Union Territory, without Legislature. It being predominantly tribal area there are very limited avenues for additional, resources mobilisation. The main sources of revenue are sale of Forest produces, power, agriculture, daisy products, rent from Government buildings, receipts of Government Distillery and State Excise, etc. Every attempt has been made by the Administration to increase the revenue receipt. The receipts have gone up from Rs. 44.99 lacs in 1974-75 to Rs. 74.90 lacs during the year 1979-80, Rs. 95.44 lacs in 1980-81 and expected to go up to Rs. 99.33 lacs and Rs. 101.26 lacs during the current yea and 1982-83 respectively.
Union Territory of Dadra and Nagar-Haveli